Mental Health Literacy Among Tertiary Education Students: Perspectives From University Students And Educators - Soo, Yue Yin (2024)
University students’ perspectives on mental health issues remain scarce despite the growing prevalence of mental illness among this population. Using a qualitative approach, this thesis explored students' perceptions and beliefs about mental health and mental illness, mental health help-seeking, as well as educators' perspectives on students' mental health literacy and their roles and challenges in supporting students' mental health. Virtual or face-to-face interviews using a semi-structured interview guide were conducted independently among university students and educators between December 2021 to July 2022. All interviews were audio-recorded, transcribed verbatim and analysed using thematic analysis. Sixteen university students and twelve educators were interviewed. Most student informants related mental health to an individual's thoughts, emotions and behaviours, while a minority equated 'mental health' with 'mental illness'. Students perceived socio-environmental factors as the primary cause of mental illness. Nearly all informants expressed positive attitudes and willingness to help people with mental illness.